Fungicide Resistance Management in West Australia’s Wheatbelt - Olita, Toto; Sung, Billy; Sharma, A.; Cao, Zhanglong; Mapulanga, Jackie; Gibberd, Mark (2025)
Barley growers from the West Australia Wheatbelt were invited to share information on their fungicide resistance management strategies. The study aimed to identify gaps in growers’ knowledge about issues like fungicide resistance and the objective and/or perceived obstacles and constraints associated with the management of fungal epidemics. To gather this information, we used a case study approach and co-designed the survey in collaboration with industry stakeholders. Socio-economic data was collected using in-depth phone interviews (which made up 82% of the responses) and self-administered questionnaires (which accounted for 18%). The data included both qualitative and quantitative responses. This data covered several aspects: growers’ demographic details, barley production statistics, current knowledge and understanding about fungicide resistance, current agronomic practices, willingness to pay to mitigate fungicide resistance risk, types of fungicide resistance management extension services growers currently use, the reasons for their preferences and additional types of fungicide resistance management extension services growers would like to access in the future.